Agency: Taking Stock of Workplace Learning Research - Goller, Michael; Paloniemi, Susanna (Research Approaches on Workplace Learning)
This chapter presents a discussion of the concept of agency. Agency is understood as a multifaceted construct describing the idea that human beings make choices, act on these choices, and thereby exercise influence on their own lives as well as their environment. We argue that the concept is discussed from three different perspectives in the literature—transformational, dispositional, and relational—that are each related to learning and development in work contexts. These perspectives do not reflect incompatible positions but rather different aspects of the same phenomena. The chapter also offers an avenue of insight into empirical studies that employ agency as a central concept as well as discussions about concepts that closely overlap with ideas of human beings as agents of power and influence.
Keywords: Agency Workplace learning Professional development Proactivity Self-direction

Supporting Young Immigrants in Their Transition From School to Work? A Staff Perspective on Challenges of Vocational Integration Classes - Goller, Michael (International Journal for Research in Vocational Education and Training)
Context: The implementation of successful measures to support immigrants' integration in cultural, social, and economic life can be considered as one of today's greatest challenges for many societies. This is especially true for adolescent immigrants who have not yet been able to finish education or gain qualifications relevant to joining the labour market. That is why many receiving countries have developed and implemented special programmes that aim at supporting immigrants' integration by facilitating their employability. Unfortunately, not much is known about the process of implementing these programmes or about how education systems, schools, and teachers are dealing with the new situation and target group. In this contribution, the implementation, development, and challenges of German Vocational Integration Classes (VIC), as an example of comparable programmes in the EU, are investigated to address this research gap. The paper considers the following exploratory research questions: (a) What challenges have been experienced by teachers and social workers in the implementation of VIC as well as in the integration of immigrants into the labour market in recent years? (b) How can these challenges be met in the long run and how should VIC be developed to better achieve its aims? Methods: To answer these questions, a sequential qualitative study containing questionnaire and interview elements was conducted. First, teachers and social workers involved in VIC filled in a questionnaire about their experiences and experienced challenges in implementing VIC (N = 46). Then, supplementing interviews were conducted with participants from the first sample in order to generate further insights and to contextualise the findings from the first study part (N = 14). Findings: From the respondents' answers, it appears that the VIC programme is well implemented. The results show, however, that central challenges continue to exist. This concerns, for example, legal regulations or the development of adequate curricula, but also the scope and quality of language education. In addition, problems have also been identified with regard to students' culture-specific education and their individual attitudes. These prevailing problems seem to affect schooling and educational processes. In addition, respondents report feeling left alone to deal with problems and that their experiences from their daily work in VIC and with immigrants are not sufficiently taken into account in policy and school-related decisions. Conclusions: Although VIC seems well implemented, key challenges remain in the view of the participants. It was found that teachers cannot solve many of the identified problems themselves, as they require action at the level of policy or school organisation. For staff, this can be accompanied by increased stress and demotivation. For the young immigrants, the existing challenges can have a long-term impact on school success and transition to vocational education and training. The study thus highlights the importance of targeted and holistic strategies to support immigrant integration through education.
Keywords: Immigration; Educational Policy; Employability; Mixed Methods; VET; Vocational Education and Training; Transitions From Education and Training to Employment

Die professionelle pädagogische Beziehung zwischen Referendar*innen und ihren Seminarlehrkräften: Belastungsfaktor oder Ressource? - Kärner, Tobias; Goller, Michael; Bonnes, Caroline; Maué, Elisabeth (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung: Der Beitrag befasst sich mit der professionellen pädagogischen Beziehung zwischen Referendar*innen und ihren Seminarlehrkräften, deren Beitrag für die Beanspruchung der Referendar*innen bisher noch nicht eingängig untersucht wurde. Das Ziel der Studie ist es, anhand einer Querschnittserhebung von 2583 Referendar*innen und ausgebildeten Lehrkräften, kompensatorische sowie verstärkende Effekte der Beziehungsdimensionen Transparenz, Fairness, Vertrauen und Ambivalenz auf die wahrgenommene Beanspruchung im Referendariat zu untersuchen. Die Analyse erfolgt mittels eines latent moderierten Strukturgleichungsansatzes. Die Ergebnisse zeigen, dass Belastungen durch die Kerntätigkeiten im Referendariat sowie Belastungen durch den Umgang mit Kolleg*innen im Lehrer*innenkollegium in signifikant positivem Zusammenhang mit resultierenden Beanspruchungsreaktionen stehen. Je transparenter, fairer und vertrauensvoller und je weniger ambivalent die Beziehung zur Seminarlehrkraft erlebt wird, desto geringer fallen die Beanspruchungsreaktionen aus. Die Ergebnisse werden hinsichtlich ihrer Relevanz für die Beziehungsarbeit im Referendariat als zentralem Ausbildungsbestandteil der zweiten Phase der Lehrer*innenausbildung diskutiert.
Keywords: Education

Augmented Reality Anwendungen in der betrieblichen Aus‐ und Weiterbildung - Kärner, Tobias; Goller, Michael; Maier, Andreas (Digitalisierung und digitale Medien in der Berufsbildung: Konzepte, Befunde und Herausforderungen)
Der Beitrag widmet sich dem Einsatz von Augmented Reality (AR) in betrieblichen Aus- und Weiterbildungskontexten. Hierbei stehen insbesondere Fragen zu Berufsfeldern und Ausbildungsinhalten, zu verwendeten AR-Spezifikationen, zu Zusammenhängen zwischen AR-Anwendung und leistungs-, wahrnehmungs- und motivationsbezogenen Variablen sowie zur didaktischen Einbettung entsprechender Technologien im Fokus. Auf Basis einer integrierenden Sichtung bestehender Literatur konnten insgesamt 16 Studien sowie zwei bereits vorliegende Literaturreviews in die Analyse eingeschlossen werden. Die Ergebnisse verweisen u. a. auf eine heterogene Lage hinsichtlich forschungsmethodischer Zugänge und didaktischer Referenzkonzepte. Weitgehend förderliche Effekte auf leistungs-, wahrnehmungs- und motivationsbezogene Variablen stimmen insgesamt bezüglich des AR-Einsatzes positiv, machen aber auch die Notwendigkeit einer integrierten Betrachtung technologischer und pädagogisch-instruktionaler Gestaltungsparameter deutlich.
Keywords: Augmented Reality; Ausbildung; Weiterbildung; Lernen mit digitalen Medien; integratives Literaturreview

Kompetenzen des betrieblichen Ausbildungspersonals: Eine literaturbasierte Systematisierung - Bonnes, Caroline; Binkert, Julia; Goller, Michael (Berufsbildung in Wissenschaft und Praxis – BWP)
Startpunkt jeglicher Professionalisierungsbemühungen ist ein Verständnis der für das professionelle Handeln notwendigen Kompetenzen. Dieser Beitrag widmet sich der literaturbasierten Identifikation von Kompetenzen des betrieblichen Ausbildungspersonals und ordnet diese den vier Kompetenzbereichen Fach-, Methoden-, Sozial- und Selbstkompetenz zu. Die Ergebnisse können sowohl als Grundlage für weitere Forschung dienen als auch in der Praxis als Orientierung für die Gestaltung von Qualifizierungsmaßnahmen verwendet werden.

Digitalization of work: Challenges for workplace learning - Harteis, Christian; Goller, Michael; Gerholz, Karl-Heinz (The SAGE Handbook of Learning and Work)
The digitalization of workplaces can introduce changes on various levels of work activities. Educational research follows this transformation in one of two ways: On the one hand, there is the optimistic perspective of expecting to improve the quality of work and work life; on the other hand, there is the expectation that conditions of work and work life will generally deteriorate. Irrespective of the concrete outcomes of digitalization, a general agreement exists that digitalization will induce changes at workplaces that affect individuals and the tasks they do. At the same time, however, scholars disagree as to whether employees experience these changes in terms of affordances that engage them into learning new processes or if they experience constraints that inhibit further engagement in learning. This chapter explores the particular developments covered under the topic of digitalization at and of work, explains particular challenges of the introduction of cyber-physical systems and analyzes consequences for workplace learning. It focuses on conceptual change as a theoretical framework for understanding the quality of learning processes that seem inevitable in order to cope with the new requirements and – more importantly – to use the potentials of the new technologies. It then sketches the poor state of empirical research conducted in this area – so far limited to exploratory field studies – even in times of corona, which has boosted the digital transformation. The chapter ends with a description of the potential and problems of – at best interdisciplinary – research into learning at digitalized workplaces.

Die Relevanz von Mentor*innen für die Professionalisierung von angehenden Lehrkräften im Praxissemester: Forschungsdesiderate und Handlungsoptionen - Caruso, Carina; Goller, Michael (Die Deutsche Schule)
Im Praxissemester (PS) sind Mentor*innen für Studierende wichtige Bezugspersonen, die sie u. a. bei der Planung, Durchführung und Reflexion von Unterricht begleiten. Während z.B. zur Kompetenzentwicklung Studierender im PS mehrere Erkenntnisse vorliegen, ist die Perspektive von Mentor*innen bisher wenig untersucht. Dieser Bericht zielt darauf, die Relevanz von Mentor*innen herauszuarbeiten, Forschungsdesiderate zu umreißen und Handlungsoptionen aufzuzeigen.
Keywords: Schlagwörter: Mentoring; Praxissemester; Professionalisierung

PLS-Based Structural Equation Modelling: An Alternative Approach to Estimating Complex Relationships Between Unobserved Constructs - Goller, Michael; Hilkenmeier, Frederic (Methods for Researching Professional Learning and Development)

Addressing Methodological Challenges in Research on Professional Learning and Development - Goller, Michael; Kyndt, Eva; Paloniemi, Susanna; Damşa, Crina (Methods for Researching Professional Learning and Development)

Q Method: Assessing Subjectivity Through Structured Ranking of Items - Leidig, Susann; Köhler, Hanna; Caruso, Carina; Goller, Michael (Methods for Researching Professional Learning and Development)

Uncovering Informal Workplace Learning by Using Diaries - Rausch, Andreas; Goller, Michael; Steffen, Bianca (Methods for Researching Professional Learning and Development)

Kompetenzerwerb auf der Schulstation: Eine Mixed-Methods-Replikationsstudie - Goller, Michael; Steffen, Bianca; Lau, D. (Professionalisierung der Gesundheitsberufe. Berufliche und hochschulische Bildung im Spiegel aktueller Forschung)

Methods for Researching Professional Learning and Development

Q Method: Assessing Subjectivity Through Structured Ranking of Items - Leidig, Susann; Köhler, Hanna; Caruso, Carina; Goller, Michael (Methods for researching professional learning and development: Challenges, applications and empirical illustrations)
Q is an exploratory method used to elicit discrete patterns of subjectivity (e.g., subjective theories, beliefs). To be more concrete, Q method aims to identify homogeneous latent clusters of viewpoints towards a certain topic from a larger more heterogeneous set of (a priori unknown) different viewpoints held by respondents in the population. For this purpose, study participants are asked to sort qualitative statements concerning a certain topic (e.g., their beliefs toward something) into a grid roughly following a normal distribution indicating whether they agree or disagree with the given propositions. This results in a so-called Q-sort for each participant that then can be fed into a factor analysis that compares the different Q-sorts and groups them by similarity. In the first part of the chapter, Q method is introduced. The second part of the chapter describes a small study focusing on student teachers and their perspectives concerning upcoming long-term school internships.
Keywords: Q method; Subjectivity; Internships; Teacher education; Q sort

Die Relevanz von Mentor*innen für die Professionalisierung von angehenden Lehrkräften im Praxissemester: Forschungsdesiderate und Handlungsoptionen - Caruso, Carina; Goller, Michael (Die Deutsche Schule)
Im Praxissemester (PS) sind Mentor*innen für Studierende wichtige Bezugspersonen, die sie u.a. bei der Planung, Durchführung und Reflexion von Unterricht begleiten. Während z.B. zur Kompetenzentwicklung Studierender im PS mehrere Erkenntnisse vorliegen, ist die Perspektive von Mentor*innen bisher wenig untersucht. Dieser Bericht zielt darauf, die Relevanz von Mentor*innen herauszuarbeiten, Forschungsdesiderate zu umreißen und Handlungsoptionen aufzuzeigen.
Keywords: Mentoring; Praxissemester; Professionalisierung / internships; mentoring; professionalisation

Erkenntnisse zur Verbesserung von Mentoringprozessen in der Lehrer:innenausbildung - Goller, Michael; Caruso, Carina; Harteis, Christian (SEMINAR – Lehrerbildung und Schule)

Zum Zusammenhang von Berufsethos und der Berufswahlmotivation angehender Wirtschaftspädagog*innen - Goller, Michael; Ziegler, Simone (bwp@ Spezial)
Sowohl Berufsethos als auch Berufswahlmotivation tragen zu relevanten lern-, leistungs- und laufbahnbedingenden Prozessen eines Individuums bei und prägen dessen Lebensverlauf wesentlich. Während die Berufswahlmotivation bereits verstärkt im wirtschaftspädagogischen Kontext untersucht wurde, existieren zum Berufsethos von Wirtschaftspädagog*innen nur vereinzelt empirische Studien. So ist beispielsweise wenig darüber bekannt, wie das Berufsethos von Wirtschaftspädagog*innen in der Ausbildungsphase ausgeprägt ist. Auch die Erforschung des Zusammenhangs zwischen den Konstrukten des Berufsethos und der Berufswahlmotivation blieb bisher unbeachtet. In diesem Beitrag wird entsprechend dieses Forschungsdesiderats untersucht, wie das anfänglich ausgebildete Berufsethos von Wirtschaftspädagogikstudierenden in der universitären Ausbildung ausgeprägt ist, ob sich die Ausprägung nach dem angegebenen Berufswunsch der Studierenden unterscheidet und inwiefern das anfänglich ausgeprägte Berufsethos mit der Berufswahlmotivation von Studierenden zusammenhängt. Dafür wurden im Wintersemester 2019/20 an zwölf deutschen Universitäten insgesamt 879 Wirtschaftspädagogikstudierende schriftlich befragt. Die Ergebnisse zeigen, dass das anfängliche Berufsethos der Befragten bereits in der universitären Ausbildungsphase relativ stark ausgeprägt ist. Weiterhin ist zu erkennen, dass das Berufsethos bei angehenden Wirtschaftspädagog*innen, die den Berufswunsch Lehrkraft haben, ausgeprägter ist als bei Wirtschaftspädagogikstudierenden, die eine Tätigkeit außerhalb des Schuldienstes anstreben bzw. noch unentschlossen sind. Letztlich kann aufgezeigt werden, dass grundsätzlich positive Zusammenhänge zwischen dem anfänglich ausgeprägten Berufsethos und der Berufswahlmotivation von angehenden Wirtschaftspädagog*innen bestehen.
Keywords: Berufsethos; Berufswahlmotivation; Wirtschaftspädagogik; Studierende

Digitalisation in Agriculture: Knowledge and Learning Requirements of German Dairy Farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal for Research in Vocational Education and Training)
Purpose: This study aims at investigating how digitalisation (in the sense of industry 4.0) has changed the work of farmers and how they experience the changes from more traditional work to digitalised agriculture. It also investigates what knowledge farmers require on digitalised farms and how they acquire it. Dairy farming was used as domain of investigation since it, unlike other industries, has strongly been affected by digitalisation throughout the last years.Method: Exploratory interviews with 10 livestock farmers working on digitalised dairy farms were analysed using qualitative content analysis. A deductive and inductive coding strategy was used. Findings: Farming work has changed from more manual tasks towards symbol manipulation and data processing. Farmers must be able to use computers and other digital devices to retrieve and analyse sensor data that allow them to monitor and control the processes on their farm. For this new kind of work, farmers require elaborated mental models that link traditional farming knowledge with knowledge about digital systems, including a strong understanding of production processes underlying their farm. Learning is mostly based on instructions offered by manufacturers of the new technology as well as informal and non-formal learning modes. Even younger farmers report that digital technology was not sufficiently covered in their (vocational) degrees. In general, farmers emphasises the positive effects of digitalisation both on their working as well as private life. Conclusions: Farmers should be aware of the opportunities as well as the potential drawbacks of the digitalisation of work processes in agriculture. Providers of agricultural education (like vocational schools or training institutes) need to incorporate the knowledge and skills required to work in digitalised environments (e.g., data literacy) in their syllabi. Further studies are required to assess how digitalisation changes farming practices and what knowledge as well as skills linked to these developments are required in the future.
Keywords: Education

Theorie-Praxis-Verzahnung in der Wirtschaftspädagogik: Potenziale und Grenzen des Lernortes Praxis - Gerholz, Karl-Heinz; Goller, Michael (Edition Fachdidaktiken)
Das Studium der Wirtschaftspädagogik bereitet Studierende auf das didaktische Handeln in beruflichen Lehr-Lernkontexten (u. a. berufliche Schulen, Ausbildung in Betrieben) vor. Theorie-Praxis-Verzahnung ist somit aus zwei Perspektiven zu modellieren: Einerseits geht es um den Aufbau eines fachwissenschaftlichen Verständnisses, welches von den Handlungszusammenhängen in einer beruflichen Domäne mit kaufmännisch-verwaltenden Bezügen ausgeht und weniger auf einer rein fachwissenschaftlichen Bildung beruht. Die zukünftige Berufspraxis der Schülerinnen und Schüler muss in den Blick genommen werden. Andererseits geht es um die Professionalisierung als pädagogisches Personal, welches berufsbezogene Lernprozesse fachdidaktisch gestalten kann. Die zukünftige Lehrpraxis in beruflichen Lehr-Lernkontexten ist in den Blick zu nehmen. Zielstellung des Beitrages ist es, diese doppelte Theorie-Praxis-Verzahnung als Konstitutionsmerkmal der Wirtschaftspädagogik aufzuzeigen (Abschn. 2), um darauf basierend anhand von Theorien des Lernens am Arbeitsplatz Potenziale und Grenzen des Lernortes Praxis als Beitrag zur Professionalisierung angehender Wirtschaftspädagog*innen im Studium herauszuarbeiten (Abschn. 3). Am Beispiel des Konzeptes von Universitätsschulen soll eine Umsetzungsvariante zur Theorie-Praxis-Verzahnung unter Herausarbeitung der Potenziale der jeweiligen Lernorte Schule und Universität aufgezeigt werden (Abschn. 4).
Keywords: Berufliche Lehrerbildung; Professional Learning; Theorie-Praxis-Verzahnung; Wirtschaftspädagogik; Universitätsschulen

Transparenz, Fairness, Vertrauen und Ambivalenz im Vorbereitungsdienst: Entwicklung eines Instruments zur Charakterisierung der professionellen pädagogischen Beziehung zwischen angehenden Lehrpersonen und deren Ausbildungslehrkräften - Kärner, Tobias; Bonnes, Caroline; Maué, Elisabeth; Goller, Michael; Schmidt, Vera (Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2021)
Wie entwickelt sich die Forschung in der Berufs- und Wirtschaftspädagogik? Das Jahrbuch gibt einen Überblick über den aktuellen Stand und bildet dadurch das breite thematische und methodologische Spektrum der Forschung und Theoriebildung im Fachbereich ab. Der diesjährige Band versammelt Beiträge, die bei der Tagung der Sektion Berufs- und Wirtschaftspädagogik der DGfE erstmalig einer breiteren Fachöffentlichkeit präsentiert wurden. Die Beiträge wurden einem Reviewverfahren unterzogen.